La teoría política del populismo: usos y controversias en América Latina en la perspectiva posfundacional. The political theory of populism: uses and debates in Latin America in post-foundational perspective - Retamozo, Martìn (Latinoamérica. Revista de Estudios Latinoamericanos, 2017)
El término populismo como concepto para los Estudios Latinoamericanos ha sido tan frecuentemente utilizado como debatido en el campo de las ciencias sociales. En los últimos años, Ernesto Laclau ha desarrollado una teoría del populismo que atrajo la atención de diferentes investigadores. Este artículo propone un estudio de la recepción y las críticas que varios teóricos políticos latinoamericanos realizaron dentro del paradigma de la teoría política posfundacional. Abstract: The term Populism, as a concept, has been widely used and debated in the field of social sciences, especially in Latin American studies. In recent years, Ernesto Laclau developed a theory about populism that aroused the interest of different researchers around the Latin American region (and around the world too). This article proposes a study regarding critiques that Latin American theorists made of Laclau ‘s theory within the paradigm of post-foundational political theory.